Average Error: 1.0 → 0
Time: 10.1s
Precision: 64
$e^{2} - e^{1}$
$\sqrt{e^{2} - e^{1}} \cdot \sqrt{e^{2} - e^{1}}$
e^{2} - e^{1}
\sqrt{e^{2} - e^{1}} \cdot \sqrt{e^{2} - e^{1}}
double f() {
double r7321511 = 2.0;
double r7321512 = exp(r7321511);
double r7321513 = 1.0;
double r7321514 = exp(r7321513);
double r7321515 = r7321512 - r7321514;
return r7321515;
}


double f() {
double r7321516 = 2.0;
double r7321517 = exp(r7321516);
double r7321518 = 1.0;
double r7321519 = exp(r7321518);
double r7321520 = r7321517 - r7321519;
double r7321521 = sqrt(r7321520);
double r7321522 = r7321521 * r7321521;
return r7321522;
}



# Try it out

Your Program's Arguments

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 1.0

$e^{2} - e^{1}$
2. Using strategy rm
3. Applied add-sqr-sqrt0

$\leadsto \color{blue}{\sqrt{e^{2} - e^{1}} \cdot \sqrt{e^{2} - e^{1}}}$
4. Final simplification0

$\leadsto \sqrt{e^{2} - e^{1}} \cdot \sqrt{e^{2} - e^{1}}$

# Reproduce

herbie shell --seed 1
(FPCore ()
:name "exp(2)-exp(1)"
(- (exp 2.0) (exp 1.0)))